Importance of general examination in diagnosis: a rare case report of a family affected with Albright’s hereditary osteodystrophy - S., Tony K.; Narwade, Ananta; Ghuge, Pooja; Sapkal, Harish; Patil, Rahul; Shingade, Pravin U.; Ambulkar, Sunil G. (International Journal of Research in Medical Sciences, 2022)
Albright’s hereditary osteodystrophy (AHO) is rare constellation of signs associated with pseudohypoparathyroidism (PHP) associated with genomic imprinting in GNAS1 gene. We described a case report of a patient with AHO phenotype with pseudopseudohypoparathyroidism (PPHP) with associated chronic liver disease and its complications and her pedigree analysis.